Identifying Indicators of Teacher Proficiency in Assessment for Learning (AfL) Frameworks - Delavarpour, Pooya; Safarnejad, Elham (Assessment and Practice in Educational Sciences, 2024)
This study aims to identify the key indicators of teacher proficiency within Assessment for Learning (AfL) frameworks based on the perspectives and practices of secondary school teachers in Tehran. A qualitative research design was employed, utilizing semi-structured interviews with 13 purposively selected secondary teachers in Tehran who actively implement AfL practices. Data collection continued until theoretical saturation was achieved. All interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis facilitated by NVivo software. The coding process involved open and axial coding, constant comparison, and regular team discussions to ensure the trustworthiness and credibility of the findings. Analysis revealed three overarching themes of teacher proficiency in AfL: (1) assessment planning and design, including alignment with learning objectives, variety of assessment methods, differentiation, clarity of assessment criteria, diagnostic assessment, and evidence-based design; (2) feedback and communication, encompassing timely, constructive, and student-centered feedback, clarity and accessibility, student involvement, ongoing communication, and sensitivity to individual differences; and (3) professional growth and reflective practice, characterized by self-evaluation, collaborative assessment culture, engagement in professional development, responsiveness to student data, and research-informed teaching. These indicators align with established models of assessment literacy and demonstrate the multifaceted nature of effective AfL practices in the classroom. This study highlights the complexity and multidimensionality of teacher proficiency in AfL, underscoring the interplay of technical, relational, and reflective competencies necessary for effective assessment. The findings support the need for targeted professional development, collaborative learning opportunities, and institutional support to foster AfL practices. Future research should broaden the scope and use mixed methods to triangulate perspectives and strengthen generalizability. Cultivating a reflective, evidence-based culture remains central to advancing AfL implementation and improving student learning outcomes.